(untitled) (Research, Society and Development, 2023)
Objective: To describe, based on the scientific literature, the main risk factors that influence the development of postpartum depression. Methodology: This is an integrative literature review, carried out in August 2022, based on: BVS, SCIELO and LILACS, where articles in the Portuguese language and period between 2016 and 2022. Results: A total of 684 articles were found, after methodological rigor through the inclusion and exclusion criteria, 13 articles were selected, 5 articles in VHL, 7 in SCIELO and 1 in LILACS, after careful evaluation of the articles, the analysis was done descriptively and predisposes the extraction of the following data: title, objective, authors/year and type of study, where all articles show risk factors for developing postpartum depression. Conclusion: Therefore, it was possible to observe that both pregnancy and the puerperium require special care to prevent and diagnose postpartum depression early, and it is necessary to recognize and seek to better manage the risk factors that trigger it, since the pregnancy period -puerperal is complex and vulnerable for women, where the multicausal changes arising from the combination of physiological, psychological, social characteristics and, in addition to the influence of genetic and environmental risk factors, can predispose her to the development of this disease.